2015
DOI: 10.11114/ijsss.v3i3.801
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Dissociation Proneness to Secondary Trauma, Burnout, and Compassion Satisfaction in Mobile Crisis Workers

Abstract: This study examined the relationship between general dissociation experiences (DES) and dissociation absorption experiences (DESAB) to secondary traumatic stress (STS), burnout (BO), and compassion satisfaction (CS). Mobile crisis workers in Maine (N = 30) anonymously completed the Dissociative Experiences Scale II and the Professional Quality of Life Scale; biographical data was masked. Results indicated high resiliency in this sample as 80% of scores reflected CS, while 24% of scores reflected STS and 7% ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Wolf and colleagues (2015) found that the dissociative and nondissociative PTSD classes did not differ on the Psychogenic Amnesia subscale, which could be expected because memory impairment is one of the core symptoms of PTSD (APA, 2013) and is likely to be elevated in all PTSD classes. The symptoms on the Loss of Awareness subscale of the DSPS were significantly more endorsed by the dissociative PTSD class than the nondissociative PTSD class in Wolf and colleagues;(2015) study, but this difference was slightly smaller than that on the Depersonalization/Derealization subscale. In our study, the effect sizes for the differences between the PTSD profile and the Dissociative profile were very similar on all DSS subscales, including Gaps in Awareness and Memory.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Wolf and colleagues (2015) found that the dissociative and nondissociative PTSD classes did not differ on the Psychogenic Amnesia subscale, which could be expected because memory impairment is one of the core symptoms of PTSD (APA, 2013) and is likely to be elevated in all PTSD classes. The symptoms on the Loss of Awareness subscale of the DSPS were significantly more endorsed by the dissociative PTSD class than the nondissociative PTSD class in Wolf and colleagues;(2015) study, but this difference was slightly smaller than that on the Depersonalization/Derealization subscale. In our study, the effect sizes for the differences between the PTSD profile and the Dissociative profile were very similar on all DSS subscales, including Gaps in Awareness and Memory.…”
Section: Discussionmentioning
confidence: 52%
“…Finally, we found that being employed is a significant predictor of the Dissociative profile. This finding is unique in the literature and could perhaps be explained by work-related stress because there is some evidence that burnout at work and dissociative experiences are positively correlated (Plouffe, 2015). However, we did not enquire about participants’ work conditions; therefore, this conclusion is speculative.…”
Section: Discussionmentioning
confidence: 80%
“…6,9 Although the term dissociation has been used to describe a wide variety of processes that should not be viewed as inherently pathological, personal proneness to detachment experienced during the course of a traumatic event, known as peritraumatic dissociation (PETD), 10 is the strongest predictor of posttraumatic stress 11,12 and confers a worse prognosis. 1 The existence of dissociation in the course of treatment for trauma patients has been associated with a broad spectrum of post-traumatic symptoms in different populations and health care settings, such as in the hospital staff after a series of sniper shootings, 13 among emergency room personnel, 14,15 among rescue workers, 10 among midwives who witnessed birth trauma, 16 among ambulance personnel, 17 among mobile crisis workers, 18 and among social workers. 19 A high level of anxiety during exposure to the traumatic experience is a mediator of the association between post-traumatic stress and PETD.…”
Section: Introductionmentioning
confidence: 99%